2020
DOI: 10.1124/mol.119.117556
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Small Molecules That Target the Phosphatidylinositol (3,4,5) Trisphosphate (PIP3)-Dependent Rac Exchanger 1 (P-Rex1) PIP3-Binding Site and Inhibit P-Rex1–Dependent Functions in Neutrophils

Abstract: Phosphatidylinositol (3,4,5) trisphosphate (PIP 3)-dependent Rac exchanger 1 (P-Rex1) is a Rho guanine-nucleotide exchange factor that was originally discovered in neutrophils and is regulated by G protein bg subunits and the lipid PIP 3 in response to chemoattractants. P-Rex1 has also become increasingly recognized for its role in promoting metastasis of breast cancer, prostate cancer, and melanoma. Recent structural, biochemical, and biologic work has shown that binding of PIP 3 to the pleckstrin homology (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…39,40 More recent studies have identified a set of small molecules against P-Rex1 by differential scanning fluorimetry, but inhibition of P-Rex1-related cell function needs to be further confirmed. 41 Liver cancer is an extraordinarily heterogeneous malignancy with a poor prognosis and a lack of curative treatments that requires continued research efforts. This study demonstrated that P-Rex1 is involved in liver cancer cell proliferation, migration, and tumor growth by modulating Akt and Erk1/2 phosphorylation via c-Met targeting.…”
Section: Discussionmentioning
confidence: 99%
“…39,40 More recent studies have identified a set of small molecules against P-Rex1 by differential scanning fluorimetry, but inhibition of P-Rex1-related cell function needs to be further confirmed. 41 Liver cancer is an extraordinarily heterogeneous malignancy with a poor prognosis and a lack of curative treatments that requires continued research efforts. This study demonstrated that P-Rex1 is involved in liver cancer cell proliferation, migration, and tumor growth by modulating Akt and Erk1/2 phosphorylation via c-Met targeting.…”
Section: Discussionmentioning
confidence: 99%
“…P-Rex1 deficiency attenuated bleomycin-induced lung inflammatory response. A combination of TGF-β1 signal pathway inhibitors with P-Rex1 inhibitor would shed light on therapeutic approaches for better pulmonary fibrosis treatment ( Lucato et al, 2015 ; Cash et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophils were isolated from human peripheral blood as described previously [56]. Freshly isolated blood was carefully layered on top of 1-step polymorphs (AN221725, Accurate chemicals and scientific corporation) (1:1 Blood and Polymorphs) and centrifuged at 1000× g for 45 min and buffy coat was transferred to fresh tubes.…”
Section: Methodsmentioning
confidence: 99%